Efektivitas Penggunaan Teknologi Artificial Intelligence (AI) dalam Pembelajaran Pendidikan Agama Islam (PAI) di SMA - Aprianti Astuti; Muhammad Nabil Priambada; Faelasup Faelasup; Nurwati Nurwati (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
The purpose of this paper is to examine the effectiveness of using artificial intelligence technology Artificial Intelligence (AI) in teaching Islamic Religious Education (PAI) in secondary schools (SMA). The method used in this research uses a library method where the literature review method is a systematic approach in collect,evaluate and synthesize literature then draw conclusions. The purpose of this writing is to find out how Artificial Intelligence (AI)dan improve PAI learning and its influence on student learning outcomes.